2014
DOI: 10.1016/j.bjbas.2014.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary study of factors affecting the superovulatory response of high producing dairy cows superstimulated regardless of the stage of estrous cycle in Egypt

Abstract: ParityPropylene glycol a b s t r a c t This work was conducted as a first time commercial production of embryos from lactating Holstein and Brown Swiss cows using multiple ovulation embryo transfer (MOET) technology in Egypt. We studied factors affecting the superovulatory response (SR) in superovulated cows and effects of propylene glycol (PG) on embryo quality. Daily milk production at flushing had significantly negative effects on SR and embryo yields in superovulated cows. In addition, Brown Swiss cows had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
3
1
2
Order By: Relevance
“…This variation might indicate the presence of a more important individual variation rather than breed influence when it comes to superovulatory treatment in bovine (Curtis, 2015). The average CL detection was comparable to previous studies for the HF crossbreeds (Ferreira et al, 2014;Vieira et al, 2014;Tadesse et al, 2016) though fewer numbers have also been reported (Hussein et al, 2014). Several other studies (Peixoto et al, 2007;Vieira et al, 2014;Mapletoft et al, 2015;Perez et al, 2016;Perez et al, 2019;Vizoná et Ethiop.…”
Section: Discussionsupporting
confidence: 85%
“…This variation might indicate the presence of a more important individual variation rather than breed influence when it comes to superovulatory treatment in bovine (Curtis, 2015). The average CL detection was comparable to previous studies for the HF crossbreeds (Ferreira et al, 2014;Vieira et al, 2014;Tadesse et al, 2016) though fewer numbers have also been reported (Hussein et al, 2014). Several other studies (Peixoto et al, 2007;Vieira et al, 2014;Mapletoft et al, 2015;Perez et al, 2016;Perez et al, 2019;Vizoná et Ethiop.…”
Section: Discussionsupporting
confidence: 85%
“…Betterridge (1997) reported that the unusual endocrine conditions after superovulation adversely affect embryo recovery and viability, and embryo recovery rates would decrease over time after ovulation. The embryo recovery rates achieved in the present study were lower than those reported in some other studies (Bülbül et al 2010;Akyol et al 2014;Hussein et al 2014;Karaşahin et al 2016). Kanagawa et al (1995) reported that the differences in embryo recovery rates between studies were related to factors such as washing time, washing media and washing number, catheter type and positioning of the catheter, technician experiences, etc.…”
Section: Discussioncontrasting
confidence: 79%
“…Furthermore, after superovulation using FSH, Köse et al (2007) reported the numbers of Grade 1 and Grade 2 embryos as 1.9±0.7 and 1.9±0.7, respectively, and indicated the number of transferable embryos as 4.1±1.0. After applying superovulation treatment with CIDR+FSH, Hussein et al (2014) reported the mean number of transferable embryos as 4.86±0.57 (68.46%), and the mean numbers of Grade 1, Grade 2 and degenerate embryos as 3.68±0.50 (50.54%), 0.90±0.30 (14.31%) and 2.33±0.40 (31.36%), respectively. In the present study, the percentages of Grade 1, Grade 2, degenerate and transferable embryos were 66.7, 22.2, 11.1 and 88.9%, respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Tingkat respon dihitung dengan membandingkan jumlah ternak yang memberikan respon superovulasi terhadap total ternak yang diberikan superovulasi. Sapi yang disuperovulasi dianggap memberikan respon apabila terdapat CL lebih dari sama dengan 3 (Hussein et al, 2014).…”
Section: Tingkat Respon (Respon Rate)unclassified
“…Diduga hal tersebut yang menyebabkan respon superovulasi pada seluruh kelompok memberikan hasil yang tidak berbeda. Hussein et al (2014) menyatakan bahwa respon ternak donor terhadap perlakuan superovulasi tergantung pada ras, umur dan kondisi umum, jenis hormon, iklim, nutrisi dan lingkungan.…”
Section: Jumlahunclassified